Crude oil prices and the euro-dollar exchange rate: A forecasting exercise - Jesus Crespo Cuaresma; Andreas Breitenfellner (University of Innsbruck, Department of Public Finance, 2008)
If oil exporters stabilize the purchasing power of their export revenues in terms of imports, exchange rate developments (and particularly, developments in the US dollar/euro exchange rate) may contain information about oil price changes. This hypothesis depends on three conditions: (a) OPEC has price setting capacity, (b) a high share of OPEC imports comes from the euro area and (c) alternatives to oil invoicing in US dollar are costly. We give evidence that using information on the US dollar/euro exchange rate (and its determinants) improves oil price forecasts significantly. We discuss possible implications that these results might suggest with regard to the stabilization of oil prices or the adjustment of global imbalances.
Keywords: Q43; F31; C53; 330; oil price; exchange rate; forecasting; multivariate time series models; Ölpreis; Wechselkurs; US-Dollar; Euro; Prognose; Zeitreihenanalyse; Welt